Efektivitas Keaktifan Visual Belajar Pendidikan Agama Kristen Melalui Penerapan Model Pembelajaran Auditory Intellectually Repetition pada Siswa Kelas XI SMA Negeri 2 Pematang Siantar Tahun Pembelajaran 2023/2024 - Jenni Trimaya Lumban Toruan; Eben Haezarni Telaumbanua; Sudirman Lase; Jungjungan Simorangkir; Lasmaria Lumban Tobing (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The purpose of this study is to determine the Effectiveness of Visual Learning Activity in Christian Religious Education through the Application of the Auditory Intellectually Repetition Learning Model for Grade XI Students of SMA Negeri 2 Pematang Siantar for the 2023/2024 Academic Year. The method used in this study is a quantitative research method with the statistics of the Pre-Experimental The One Shot Case Study. The population is all students in grade XI of SMA Negeri 2 Pematang Siantar and a sample of 31 people with purposive sampling techniques or samples taken intentionally. Data was collected with a questionnaire of 26 items. The results of the data analysis show that there is an Effectiveness of Visual Learning Activity in Christian Religious Education through the Application of the Auditory Intellectually Repetition Learning Model for Grade XI Students of SMA Negeri 2 Pematang Siantar for the 2023/2024 Academic Year. The analysis requirements test are –ttable = -2.042 > tcal = 9.856 > ttable = 2.042. It is known that the tcount value is at the area of rejection of H0 and acceptance of Ha, then H0 is rejected and Ha is accepted. Thus, it can be concluded that there is an increase in the Effectiveness of Visual Learning Activity of Christian Religious Education through the implementation of the Auditory Intellectually Repetition Learning Model, which is 86.55 in the post-test and 69.32 in the pre-test in Grade XI Students of SMA Negeri 2 Pematang Siantar for the 2023/2024 Academic Year.